2015
DOI: 10.1186/s13256-015-0772-8
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated tuberculosis presenting as hemophagocytic lymphohistiocytosis in an immunocompetent adult patient: a case report

Abstract: BackgroundHemophagocytic lymphohistiocytosis is a frequently fatal and likely underdiagnosed disease. It is a rare occurrence in adults and usually secondary to an insult such as viral infections, bacterial infections, autoimmune connective tissue disorders, malignancies and immunocompromised states, in contrast to its childhood counterpart, which is due to a genetic defect but may share some of same genetic etiologies. It is characterized by multisystem inflammation due to unregulated proliferation and infilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…We further analyzed 18 more cases published since 2014, including our case, along with the previously published cases. [8][9][10][11][12][13][14][15] Our analysis showed that of 82 patients, 58.5% were men, and the median age of presentation was 40 years. The patients presented with a median duration of 35 days, and all had fever (100%), while majority had hepatomegaly (70%), splenomegaly (77.9%), and lymphadenopathy (62.2%) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…We further analyzed 18 more cases published since 2014, including our case, along with the previously published cases. [8][9][10][11][12][13][14][15] Our analysis showed that of 82 patients, 58.5% were men, and the median age of presentation was 40 years. The patients presented with a median duration of 35 days, and all had fever (100%), while majority had hepatomegaly (70%), splenomegaly (77.9%), and lymphadenopathy (62.2%) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The term familial hemophagocytic reticulosis was then changed to primary or familial HL and subsequently, nongenetic causes were recognized (i.e., secondary HLH) [1,4]. While primary HLH consists of different monogenic alterations that derive from impaired cytotoxicity of natural killer cells (NK) and CD8+ cytotoxic T lymphocytes (CTL), secondary HLH presents as an acquired complication in several contexts such as infections, malignant neoplasms, autoimmune diseases, post-transplantation, or is iatrogenically induced (Table 1) [8,9,10,11,12,13,14,15]. Regardless of the etiology, HLH is characterized by an uncontrolled activation of NK/CTL that provokes the release of large amounts of proinflammatory cytokines such as IFN-γ, TNF-α, GM-CSF, M-CSF, and IL-2, resulting in hyperstimulation and systemic infiltration by macrophages which, in turn, phagocytose blood cells, mostly red blood cell precursors, and secrete other cytokines responsible for myelosuppression, endothelial damage with coagulopathy, tissue injury, and NK/CTL incessant activation (IL-1, IL-6, and TNF-α) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterium tuberculosis infection is a known rare trigger of sHLH [13] in immunocompromised patients. The man's occupation, his prolonged steroid therapy and HCL were all significant risk factors for MTB infection, which developed atypically without pulmonary lesions and without detection of MTB-DNA on bronchial wash fluids.…”
Section: Discussionmentioning
confidence: 99%